A grassroots approach for greener education: An example of a medical student-driven planetary health curriculum - Navarrete-Welton, Allison; Chen, Jane J.; Byg, Blaire; Malani, Kanika; Li, Martin L.; Martin, Kyle Denison; Warrier, Sarita (Frontiers in Public Health, 2022)
The adverse health effects of human-driven environmental change have been thoroughly documented and in recent years, increasing attention has been paid to including these factors in medical education. However, the logistics of creating and implementing planetary health educational programs into medical school curricula can be daunting. While some groups have proposed top-down approaches driven by sets of overarching principles, this article presents the bottom-up student-driven approach to planetary health education undertaken at the Warren Alpert Medical School of Brown University. Here, student advocacy led to the creation of a task force composed of faculty, administrators, and students that developed a set of school-wide interventions intended to equip all graduates with a set of planetary health core competencies as well as additional opportunities for motivated students to deepen their learning. Importantly, the core competencies of the planetary health curriculum were designed to fit within the Medical School’s existing pedagogical framework, the Nine Abilities. This approach clearly demonstrated planetary health’s place in medical education and thus facilitated its implementation. In this article, we explain the task force structure, projects undertaken, and lessons learned with the intention of providing a framework for other medical schools interested in improving their planetary health curricula.